Longitudinal assessment of heavy alcohol use and incapacitated sexual assault: A cross-lagged analysis. (June 2019) - Norris, Alyssa L.; Carey, Kate B.; Walsh, Jennifer L.; Shepardson, Robyn L.; Carey, Michael P.
Abstract: Researchers have argued there are bidirectional associations between heavy alcohol use and sexual assault; however, research in this area is inconclusive due to methodological differences, particularly in study design. The purpose of this study is to clarify the longitudinal associations between heavy alcohol use and incapacitated sexual assault among first-year college women, accounting for hypothesized autoregressive effects within each construct over their first year of college. A sample of 483 women completed regular surveys that assessed a range of health behaviors, including alcohol use and sexual behavior, during their first year of college. We used cross-lagged analyses to examine prospective associations between incapacitated sexual assault and heavy alcohol use (frequency of heavy episodic drinking and peak blood alcohol content). There were significant autoregressive effects, such that women who were engaging in heavier alcohol use as they entered college continued to be heavier alcohol users throughout their first year, and women with a history of assault at college entry were at greater risk for assault during their first year of college. There was a significant cross-lagged effect from precollege incapacitated assault to first-semester alcohol use after controlling for pre-college alcohol use. There were no significant cross-lag paths from alcohol use to subsequent incapacitated assault. Women with a history of incapacitated sexual assault engaged in heavier drinking during their transition to college, but heavy alcohol use did not predict subsequent assault risk. Highlights: Sexual assault prior to college is a robust predictor of sexual assault during college. Sexual assault prior to college is associated with increases in heavy drinking as women transition into college. Heavy alcohol use was not associated with subsequent assault risk over time.